2020
DOI: 10.3390/nu12041094
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake of Free Sugars is Associated with Disease Activity and Dyslipidemia in Systemic Lupus Erythematosus Patients

Abstract: Diet has been closely associated with inflammatory autoimmune diseases, including systemic lupus erythematosus (SLE). Importantly, the consumption of dietary sugars has been positively linked to elevated levels of some inflammation markers, but the potential role of their consumption on the prognosis of autoimmune diseases has not yet been examined. The aim of this study was to evaluate the association between the dietary intake of free sugars and clinical parameters and cardiovascular (CVD) risk markers in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 41 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…In this study, we demonstrate that dietary modulation of protein intake has little impact on IMQ-induced psoriasis-like skin disease but nevertheless impacts systemic inflammation. The association between diet and the risk of developing inflammatory autoimmune diseases such as rheumatoid arthritis [34,35], multiple sclerosis [36], systemic lupus erythematosus [37], or inflammatory bowel disease [38] was proposed more than 50 years ago. The widespread "Western diet" (high-fat and cholesterol, high-sugar, and excess salt intake) not only drives obesity, metabolic syndrome and cardiovascular disease, but has also been suspected as a crucial driver for almost all autoimmune diseases [39].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we demonstrate that dietary modulation of protein intake has little impact on IMQ-induced psoriasis-like skin disease but nevertheless impacts systemic inflammation. The association between diet and the risk of developing inflammatory autoimmune diseases such as rheumatoid arthritis [34,35], multiple sclerosis [36], systemic lupus erythematosus [37], or inflammatory bowel disease [38] was proposed more than 50 years ago. The widespread "Western diet" (high-fat and cholesterol, high-sugar, and excess salt intake) not only drives obesity, metabolic syndrome and cardiovascular disease, but has also been suspected as a crucial driver for almost all autoimmune diseases [39].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, simple and digestible carbohydrates (e.g., sucrose, fructose, and glucose) are also indicated to modulate microbial diversity. Furthermore, they would impair gut permeability [ 68 , 69 ]. Fajstova et al showed that a diet rich in simple sugars (high-sugar diet or HSD) induced an alteration in gut microbial composition and inflammatory immune responses in mice and that the HDS-fed mice showed increased severity of experimental colitis [ 68 ].…”
Section: Modulation Of the Gut And Oral Microbiome By Glucosementioning
confidence: 99%
“…Fajstova et al showed that a diet rich in simple sugars (high-sugar diet or HSD) induced an alteration in gut microbial composition and inflammatory immune responses in mice and that the HDS-fed mice showed increased severity of experimental colitis [ 68 ]. In the field of autoimmune diseases, it has been reported that dietary free sugar intake was associated with the disease activity of systemic lupus erythematosus (SLE) [ 69 ], which indicates a possible role for sugar intake in SLE and other autoimmune rheumatic diseases. Thus, as described by Anhê et al [ 70 ], the relationship between blood glucose and gut microbes is bidirectional.…”
Section: Modulation Of the Gut And Oral Microbiome By Glucosementioning
confidence: 99%
“…In comparison, 5% was associated with a better outcome, a strategy adopted by the Scientific Advisory Nutrition Committee (Moynihan and Kelly 2014;SACN 2015). Although there are some inconsistencies in the field, sugar intake has been associated with several disease outcomes, including CVD (Te Morenga et al 2014;Dinicolantonio and Okeefe 2017), diabetes, and autoimmune diseases (Zhang et al 2019;Correa-Rodríguez et al 2020). Moreover, data from animals study show that a Western diet rather than a high-fat diet can lead to a psoriasis-like phenotype which occurs earlier than obesity, suggesting that sugars' effect on health is independent of obesity (Shi et al 2020).…”
Section: Free Sugarsmentioning
confidence: 99%